Pertanggungjawaban Pejabat Pembuat Akta Tanah Dalam Kesalahan Mengikuti Prosedur Pembuatan Akta Autentik (Studi Putusan Nomor 250/Pid.B/2021/PN.Jkt.Brt) (Lembaga Pengembangan Kinerja Dosen, 2025)
This study examines the liability of notaries who are defendants in court for committing the crime of forgery of authentic deeds and the crime of money laundering by dissecting Decision Number 250/Pid.B/2022/PN.Jkt.Brt. This was done intentionally by involving several parties, including other notaries and without the knowledge of interested parties. This study uses a normative juridical approach which includes a statutory approach and a case approach. The results of the study found that the defendant who served as a notary intentionally neglected to carry out procedures in making an authentic deed as if the deed was actually made, such as signing the deed, giving a deed number, and using a stamp. In addition, the defendant did not read out the contents of the deed in front of the parties, where the parties intentionally committed a criminal offense. As a result, notaries are not only responsible for their actions in the criminal realm, but also in the civil and administrative realms. In the criminal case, the defendant was proven to have falsified the authentic deed and committed the crime of money laundering because he received payment for his unlawful actions.